The dynamics of inflation and currency substitution in a small open economy - Freitas, Miguel Lebre de (2004)
The Dynamics of Inflation and Currency Substitution in a Small Open Economy Abstract: In this paper, we analyse the relationship between money and inflation in a small open economy where domestic and foreign currencies are perfect substitutes as means of payment. It is shown that, if the path of domestic money supply is such that individuals find it optimal to change the currency in which transactions are settled, there will be an adjustment period during which domestic inflation adjusts so as to equalise the foreign inflation rate. In the case of a disinflation program, it is shown that the foreign currency is not necessarily abandoned as means of payment. The results obtained are consistent with both dollarisation hysteresis and reversibility, without requiring the specification of dollarisation costs.